PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ASSEMBLR EDU PADA MATERI SUMBER DAYA ALAM HAYATI DI SDN 8 MUARA PINANG - Shefa Nurjannah; Sukardi; Mega Kusuma Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to obtain assemblr edu-based learning media on natural resources material that has been tested for validity and practicality to improve the quality of learning at SDN 8 Muara Pinang. This study uses a research and development method (Research and Development) with the ADDIE model research steps, namely Analyze, Design, Development, Implementation and Evaluation. Data collection techniques in this study are observation, interviews and questionnaires (validity test questionnaires and practicality test questionnaires). Research results (1) Based on the results of the validity test questionnaire conducted by experts, assemblr edu-based learning media received a score of 75.00% from media experts, 95.00% from material experts and 95.00% from language experts. From these values, an average percentage of 88.33% was obtained and categorized as